Hubungan Rinitis Alergi Dengan Kejadian Sinusitis Di Rsud Dr Doris Sylvanus - Angeline Novia Toemon; Muhamad Umar Muhtar Hasan; Arif Rahman Jabal; Astrid Teresa; Rian Ka Praja (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Sinusitis is an inflammation of the paranasal sinus mucosa and is one of the world's health problems and is often found in medical practice. The National Health Interview survey in 2012, found that 12% of the total sample of 34,525 adults experienced sinusitis. Allergic rhinitis is one of the factors causing sinusitis due to bacterial infection of the sinus tract due to blockage of the sinus ostium and mucus that cannot be drained due to allergic reactions. This study aims to analyze the relationship between allergic rhinitis and the incidence of sinusitis in patients at RSUD dr Doris Sylvanus Palangka Raya. This research is an analytical observational study with a cross section study design conducted at RSUD dr Doris Sylvanus Palangka Raya. The subjects in this study were patients with a history of allergic rhinitis and sinusitis for the period 2021-2023 who met the inclusion and exclusion criteria. There were 271 research samples where the statistical test showed a p value = 0.000 and OR = 0.092. Allergic rhinitis has an association with sinusitis and allergic rhinitis has a chance of developing sinusitis.